EVALUASI PEMBELAJARAN PENDIDIKAN KEAKSARAAN FUNGSIONAL BERBASIS KOMPETENSI SEBAGAI WAY OF LIFE WARGA BELAJAR: Studi Evaluasi - Rasid Larasi (Jurnal AKRAB, 2020)
Abstract: Literacy education as a way of life, for all groups so that it can exist in his life. This goals of study to reveal how well the competencies of citizens studying literacy education correlate with aspects of life. The research method uses an evaluation study that aims to find out how well the achievement of learning competencies of citizens in the learning program period. The study was conducted in Southeast Sulawesi with a tiered sampling method, random sampling, with a sample of 350 people studying functional adult literacy education. Research Time January to March 2020. The results of the study stated that literacy learning in adults has a significant effect on the functional competencies of life of learning citizens namely (1) competence to motivate self-learning citizens; (2) competence in doing family micro business; (3) competence has practical skills; (4) competence to access employment; (5) competence in a healthy lifestyle; (6) competence in communicating using Indonesian; (7) competence in the use of technology in daily life; (8) environmental preservation competencies; (9) disaster mitigation competencies; (10) competency obligations and rights as citizens; (11) cultural preservation competencies; (12) physical fitness and recreation competency.